Sequitur Algorithm For Particular Character Compression Or Words Always Returned - Efori Buulolo (The IJICS (International Journal of Informatics and Computer Science), 2017)
Character pairs or recurrent words are often found on large documents. The document uses a large space in storage. At this time the storage with a large amount of space is not a problem anymore, with the availability of various media types of large data storage media and the price is very affordable. Although in the form of storage media is not a problem but in the storage and transmission of data, a large document would need an efficient for storage space and so does the case of data transmission. The Sequitur algorithm is one suitable algorithm for concluding context-free grammar into a compression to reduce repetitive input. The Sequitur algorithm is perfect for large document compression with paired or repeated characters so that the document uses more efficient storage space in the case of data transmission